Interface-controlled creep in metallic glass composites. (December 2017) - Kalcher, Constanze; Brink, Tobias; Rohrer, Jochen; Stukowski, Alexander; Albe, Karsten
Abstract: In this work we present molecular dynamics simulations on the creep behavior of Cu64 Zr36 metallic glass composites. Our results reveal that all composites exhibit much higher creep rates than the homogeneous glass. This is because the glass–crystal interface acts like a weak interphase, where the activation of shear transformation zones is easier than in the surrounding glass. We observe that the creep behavior of the composites does not only depend on the interface area but also on the orientation of the interface with respect to the loading axis. We propose an explanation in terms of different mean Schmid factors of the interfaces, with the amorphous interface regions acting as preferential slip sites. Graphical abstract: Image 1